The giant encyclopedia of transition activities for children 3 to 6 : over 600 activities created by teachers for teachers / For Children 3 to 6 : Over 600 Activities Created by Teachers for Teachers - Charner, Kathy; Murphy, Maureen; Ford, Jennifer, 1980- (Beltsville, Md. : Gryphon House, 2005)
"Resource book with over 600 transition activities for teachers of preschool children ages three to five to use in the classroom"--Provided by publisher.
Includes indexes.
Keywords: Education, Preschool -- Activity programs -- Encyclopedias